Adenomas of the pituitary gland: Diagnostic challenges, pitfalls and controversies - Roncaroli, F; Faustini-Fustini, M; Bravi, I; Ansorge, O (2011)
Pituitary adenomas account for about 10% of intracranial tumours and 90% of intrasellar lesions. They are classified according to histopathological and ultrastructural features and hormone immunoexpression but a comprehensive diagnosis requires a full knowledge of clinical and neuroimaging features. If the common histotypes can be easily identified at light microscopy, the diagnosis of rare variants can be challenging and may require ultrastructural examination or the use of more sophisticated immunostains. Similarly challenging and source of diagnostic pitfalls can be the changes that may occur during surgery or following medical treatment. Finally, controversies still surround the concept of atypical adenoma and pituitary carcinoma making a histopathological diagnosis of aggressive adenoma very difficult. This review will provide the essential diagnostic criteria to recognise rare adenoma variants and will address the questions of a diagnosis of adenoma with aggressive behaviour. © 2011 Elsevier Ltd.